Evaluation of integrated modular teaching in Chinese ophthalmology trainee courses - Xin, Wei (BMC Med Educ, 2020)
BACKGROUND: Before attending ophthalmology trainee courses in Zhongshan Ophthalmic Centre, the medical students from Sun Yat-sen University had finished two years of premedical education after the six-year medical courses including basic medical courses, clinical medical courses, clerkship, and research training in medical college. Integrated modular teaching using different problem-based teaching methods in ophthalmology was designed by the teaching steering committee of Zhongshan Ophthalmic Centre. This study aimed to evaluate the effectiveness and satisfaction scales of the integrated modular teaching among the trainee students. METHODS: A total of 100 medical students attending ophthalmology trainee courses in Zhongshan Ophthalmic Centre were enrolled and randomly allocated into 4 groups according to the teaching arrangement. The trainee courses consisted of several sessions delivered in multiple methods, such as “flipped classroom” session and team-based learning session. The pre- and post-class tests were delivered to evaluate the effectiveness of the integrated modular teaching. The satisfaction survey questionnaire was collected from all participants to investigate the degree of satisfaction. RESULTS: Compared with the first-day-test score, the total last-day-test score was significantly improved by a paired t-test (t = 3.288, P = 0.001). Nineteen students obtained a significant improvement in ranking increased by more than 10 in the last-day-test, whereas they failed to obtain a higher average score for daily performance than other students (t = 0.469, P = 0.654). According to the participant satisfaction questionnaires, these innovative teaching methods were considered as effective and satisfactory. CONCLUSIONS: Integrated modular teaching in ophthalmology trainee courses is effective and appreciated by the medical college students.